2021
DOI: 10.3390/ph14030242
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cationic Meso-Arylporphyrins and Their Antiviral Activity against HSV-1

Abstract: This work is devoted to the search for new antiherpes simplex virus type 1 (HSV-1) drugs among synthetic tetrapyrroles and to an investigation of their antiviral properties under nonphotodynamic conditions. In this study, novel amphiphilic 5,10,15,20-tetrakis(4-(3-pyridyl-n-propanoyl)oxyphenyl)porphyrin tetrabromide (3a), 5,10,15,20-tetrakis(4-(6-pyridyl-n-hexanoyl)oxyphenyl)porphyrin tetrabromide (3b) and known 5,10,15,20-tetrakis(1-methyl-4-pyridinio)porphyrin tetraiodide (TMePyP) were synthesized, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Although we found that the compound induces massive cell death when activated by light at concentrations >1 μM, low systemic toxicity was observed in the nanomolar range, which is comparable to other similar compounds [ 45 , 46 , 47 ]. This allowed us to design antiviral assays at subtoxic concentrations, which is highly important to avoid toxicity concerns and to extend the potential application to the inactivation of different viruses in sensitive biological materials (e.g., serum or blood).…”
Section: Discussionsupporting
confidence: 53%
“…Although we found that the compound induces massive cell death when activated by light at concentrations >1 μM, low systemic toxicity was observed in the nanomolar range, which is comparable to other similar compounds [ 45 , 46 , 47 ]. This allowed us to design antiviral assays at subtoxic concentrations, which is highly important to avoid toxicity concerns and to extend the potential application to the inactivation of different viruses in sensitive biological materials (e.g., serum or blood).…”
Section: Discussionsupporting
confidence: 53%
“…Trans-A2B2 type dicationic porphyrins 31a,b in the form of free base and zinc complex [136] were used to study the effect of the PS structure on photodynamic antibacterial activity. In the study of the photoinduced antibacterial activity of these porphyrins against Staphylococcus aureus strain 78 zinc complex 31b was found to exhibit photodynamic action within the whole concentration range studied, even at a minimum irradiation dose of 2.3 J/cm 2 compared to the free-base porphyrin, which showed lower effi- The antiviral activity of compounds 29a,b against the herpes simplex virus 1 (HSV-1) was also evaluated in our work [137]. Compounds 29a,b and their Pluronic F-127 micellar forms showed virucidal efficiency and affected the different replication stages of HSV-1.…”
Section: Other Cationic Derivativesmentioning
confidence: 80%
“…In our studies [134][135][136][137], we investigated the antimicrobial activity against S. aureus and E. coli bacteria and their biofilms for cationic meso-arylporphyrins with A4 and AB-AB structure with terminal pyridinium groups (Figure 15). In these works, we modified the following parameters in the structure of the compounds: (1) the hydrophilichydrophobic balance varied depending on the number of methylene spacers (2, 4, 5, 10); In our studies [134][135][136][137], we investigated the antimicrobial activity against S. aureus and E. coli bacteria and their biofilms for cationic meso-arylporphyrins with A4 and ABAB structure with terminal pyridinium groups (Figure 15). In these works, we modified the following parameters in the structure of the compounds: We have shown that the efficiency of the used РS decreases with the increasing length of the methylene spacers, which is associated with an increase in their hydrophobicity, and hence with the aggregation processes in aqueous media.…”
Section: Other Cationic Derivativesmentioning
confidence: 99%
“…Furthermore, this study evaluated the cytotoxicity and antiviral activity of porphyrin and por-CDs against SARS-CoV-2 in mammalian cells. On Vero E6 cells, the CC 50 of porphyrin used in this study (15.5 μg/mL, equivalent to 49.94 μM where the molecular weight of porphyrin is 310.352 g/mol) was much higher than the other porphyrin derivatives: verteporfin (10.33 μM) [ 43 ], Sn-protoporphyrin IX (20.7 μM) [ 55 ], and a novel meso-arylporphyrin (43 μM) [ 56 ]. Nonetheless, it is still below the standards for cytotoxicity of plant extracts on mammalian cells [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%